2015
DOI: 10.1002/ams2.99
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prolonged laparoscopic cholecystectomy in the treatment of low‐grade acute cholecystitis: a single‐center, retrospective, observational study

Abstract: Aim: Laparoscopic cholecystectomy is frequently used to treat low-grade acute cholecystitis. Improvements in technical skills have reduced the rate of conversion from laparoscopic to open surgery. In this study, we sought to identify factors that might predict the surgical time of laparoscopic cholecystectomy as possible markers for surgical difficulty. Methods:We carried out a single-center retrospective analysis of a Japanese medical insurance database. Data were retrieved for 87 patients with acute cholecys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…3 Many investigators have reported risk factors that account for the surgical difficulty, conversion to open cholecystectomy, prolonged surgical duration, or postsurgical complications in patients diagnosed with AC. In these patients, risk factors accounting for the experienced surgical difficulties vary and include gallbladder wall thickening, [6][7][8] cystic duct impaction, 7 elevated presurgical CRP, [10][11][12] higher BMI of patients, 9,13 sex (male patients), 6,14 and longer duration between symptom onset and surgery. 14 The definition of surgical difficulty in patients diagnosed with AC also varies based on published reports.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Many investigators have reported risk factors that account for the surgical difficulty, conversion to open cholecystectomy, prolonged surgical duration, or postsurgical complications in patients diagnosed with AC. In these patients, risk factors accounting for the experienced surgical difficulties vary and include gallbladder wall thickening, [6][7][8] cystic duct impaction, 7 elevated presurgical CRP, [10][11][12] higher BMI of patients, 9,13 sex (male patients), 6,14 and longer duration between symptom onset and surgery. 14 The definition of surgical difficulty in patients diagnosed with AC also varies based on published reports.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, risk factors evaluated via a presurgical CT scan vary. Among these factors, CT attenuation, 22 absence of gallbladder wall enhancement, presence of a gallstone in the gallbladder infundibulum, 23 edema in the gallbladder wall, 13 and dirty fat signs 24 have been reported. However, to the best of our knowledge, none of the reports indicated that the maximum diameter of the gallbladder measured via a CT scan was a risk factor for difficult LC in patients with AC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations